Cash Holdings in Indonesia’s Consumer Goods Sector - Nafa Yuliastri; Syifa Nurlita Sari; Farah Margaretha Leon (Universitas Kristen Maranatha, 2026)
Purpose – This study aims to analyze the factors that influence cash holdings in non-cyclical consumer goods companies listed on the Indonesia Stock Exchange during the period 2020-2024. Design/Methodology/Approach – This study uses quantitative methods with secondary data from the financial statements of 33 non-cyclical consumer goods companies listed on the Indonesia Stock Exchange during 2020-2024 (165 observations). The data were analyzed using panel regression with the Fixed Effect Model (FEM), selected based on the Chow and Hausman tests, using EViews 9. Findings – The results show that cash flow, net working capital, Tobin’s Q, and leverage have a significant positive effect on cash holdings. Meanwhile, firm size and capital expenditure have a significant negative effect on cash holdings. Profitability, financial performance, and book value have no significant effect. Research limitations/Implications – The results of this study provide practical implications for financial managers and investors in optimizing cash management strategies to maintain liquidity and support corporate financial stability, which ultimately contributes to the growth and resilience of the manufacturing sector in the national economy. Keywords: Cash Flow, Cash Holding, Firm Size, Leverage, Net Working Capital, Tobin’s Q